Implementation of SWOT Analysis in Marketing Strategy for Murabahah Finance Products PMG-ASN Motorcycles During COVID-19 Pandemic - Kevin Mifthah Hadi Lubis; Nuri Aslami (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
This study's findings include a marketing strategy, specifically the marketing of PMG-ASN Motorbike Murbahah financing products, implemented by PT. Bank Sumut during the Covid-19 pandemic, which includes several strategies, namely: picking up balls, building networks, providing excellent service, and providing satisfying facilities to increase customer trust and satisfaction so that custodians feel secure. According to the SWOT analysis findings, PT. Bank Sumut has taken the risk of competing in a competitive market while offering customers innovative products. SO Strategy (potentially lucrative opportunities): Expanding market share, expanding collaboration with motorcycle dealers in North Sumatra, and building relationships with academics, government officials, and business leaders. WO strategy (Weakness Opportunities): Specifically, implementing a ball pick strategy, enhancing consumer loyalty, and improving product quality are examples of WO strategies. An ST strategy (strengths Treats) involves partnering with government departments and dealers to define marketing objectives and improve service quality. A second technique is executing more excellent promotion through various media and establishing an effective and efficient marketing plan (Weakness Treats / WT).Keywords: Covid-19 pandemic, marketing strategy, motorcycle PMG- ASN products, SWOT